Optimization of municipal solid waste conversion technology using process network synthesis - Ali, Rabiatul Adawiyah; Nik Ibrahim, Nik Nor Liyana (Centre for Environmental Sustainability and Water Security (IPASA), Universiti Teknologi Malaysia, 2019)
The number generation of municipal solid waste (MSW) is increasing year by year all around the world including Malaysia. For now, it still a big concern in Malaysia since we only dispose our MSW on landfills. Process Network Synthesis (PNS) is a tool to optimize technologies conversion of MSW. This study optimizes MSW conversion technologies using PNS tool which is Process Graph (P-Graph). Four highest composition (food waste, agriculture waste, paper and plastics) of MSW generated in Malaysia are optimized using P-graph. Two types of technologies conversion are considered which are biological conversion (Anaerobic Digestion) and thermal conversion (Pyrolysis and Incinerator). All these technologies conversion is compared with common method used; landfill. 100 feasible structure have been generated using P-graph. These optimization models allowed analysis of economic performance and environmental impact of MSW conversion technologies. Out of 100, 9 feasible structures have been analysed. Two feasible structures are selected based on maximum economic performance and minimum environmental impact.